Iodine in Nigeria: A Review of Concepts; Prevalence, and Effect on Brain Cognitive Potential - Aminu Umar Imam; Yusuf Sarkingobir (Pancasakti Journal Of Public Health Science And Research, 2025)
The issue of iodine deficiency is a historic threat that affects all regions of the world. Iodine is a critical element belonging to the halogens that is used to make vital hormones (thyroid hormones) for the proper functioning of the human or mammalian body. Iodine is obtained from the diet of either plant or animal origin or water. Iodine for plants uptake is obtained from soil, which is affected by the nature of the environment such as climate, locations, topography, iodine fixation potential, proximity to sea and relations. The failure of the proper iodine cycling spurs a poor intake by humans. Poor dietary intake of iodine occurs at different levels, but the entire complex dealing with poor iodine intake is termed as iodine deficiencies, such as goiter, cretinism, hypothyroidism, and hyperthyroidism. Effects resulting from iodine deficiency are many and enormous. The iodine deficiency among other things affect the brain (nervous system functioning) probably because it affects the whole body metabolism when thyroid hormones are insufficient, and neurotransmitters and oxidative stress regulations are limited. It is important to deliberately educate the public, fortify foods properly, give iodine supplements, monitor iodine deficiencies, and utilize diverse foods; because IDD cause mental retardation among other things.